PjBL-based digital history model to improve historical concept skills and historical consciousness - Matitaputty, Jenny Koce; Saputra, Nanda; Judijanto, Loso; Susanto, Nugroho; Hanif, Muhammad; Sopacua, Jems; Fadli, Muhammad Rijal (Intelektual Pustaka Media Utama, 2024)
Digital history-based project-based learning (PjBL) in history learning is a learning medium that can provide a special attraction for students who can improve historical concept skills and historical awareness. However, there are still many teachers who have not used it, so it is very important to study it. This research aims to analyze the influence of the digital history based PJBL model in improving historical concept skills and historical awareness. The method used is quasi-experimental with two classes, experimental and control. The population used class XI high school students in Lampung, Indonesia and the sample size was 213. Cluster random sampling was used to determine sampling, while data collection was in the form of test instruments. The test instrument questions were analyzed using the gain score and Kruskal-Walli’s test to determine the increase in historical concept skills and historical awareness with the help of statistical package for the social sciences (SPSS) 26. The research results confirmed that digital history based PjBL was effective in increasing historical concept skills and historical awareness with a high score, making it the best choice to overcome obstacles in history learning.